Pembatalan Perjanjian Sewa Gedung Pernikahan Akibat Pandemi Covid-19 - Septini Anriwati; Dwi Aryanti Ramadhani (Universitas Batanghari Jambi, 2021)
Agreement / contract is a legal relationship that is often carried out in the business world / community in Indonesia. With the issuance of the Presidential Decree which stipulates the Corona Virus (COVID19) as a national disaster it has had an impact on all aspects of community life then the local government issued a large-scale social restriction (PSBB) regional regulation. With the decision of Covid-19 as a national disaster emergency, restrictions and / or restrictions on activities in the community were imposed, which resulted in the cancellation of the building lease agreement for wedding receptions which could result in default in fulfilling the rights of the Parties. The research was conducted by using the normative juridical method and the specification using descriptive analytical. research methods that are research methods that use an approach based on the main legal materials by examining theories, concepts, legal principles and laws and regulations related to this research. The results of the research and discussion show that Covid-19 can be categorized as a force majeure which can be a reason for the cancellation of an agreement to rent a building. So that a renegotiation is needed in order to fulfill the obligations of the Parties in leasing a building.